Reality Lost: Markets of Attention, Misinformation and Manipulation - Hendricks, Vincent F. (Springer Nature, 2019)
Attention Economics; Conspiracy Theory; Philosophy; Democracy; Information; Digital Authority; Digitial Slavery; Donald Trump; Information Age; Misinformation; Politics; Populism; Social Media